The Roles of Artificial Intelligence (AI) towards Students’ Communication Strategy in ESP Maritime English - Munir, Ahmad; Anam, Syafi’ul; Ratnaningsih, Dyah (Asian Journal of Applied Education (AJAE), 2025)
Globalization has boosted economic growth, making shipping the most vital mode of transportation and highlighting the need for competent, English-speaking seafarers. So, maritime academy students must be proficient in oral Maritime English (ME) to ensure clear communication and prevent mishaps. This study explored the roles of Artificial Intelligence (AI)  towards the communication strategies used by students. Using a mixed-methods design, data were collected through speaking activity observations and semi-structured interviews. Before using AI, students relied on strategies like topic avoidance, message abandonment, approximation, code-switching, and stalling. After AI integration, more effective strategies emerged, such as approximation, clarification-seeking, stalling, and self-correction. The roles of AI towards students’ communication strategy were helping them to avoid literal translation, rely less on others, eliminate message abandonment, and reduce stalling, leading to improved fluency, independence, and professional communication in maritime contexts.